Synthesis and electrical properties of novel supramolecular octa-phthalocyaninato-dicobalt(II)-hexazinc(II) and dicobalt(II)dimeric-phthalocyanine with six ferrocenylimin pendant groups - ABDURRAHMANOĞLU, ŞAZİYE (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
In this study supramolecular octakis phthalocyaninato-diCo(II)hexakis-Zn(II) has been synthesized in two steps. Starting with tetracyanodibenzo(1,4,7,10-tetrathia7(12-crown)) (1) and 4-nitro-1,2-dicyanobenzenc (2), nitro-substitutcd dimeric phthalocyanine (3) was synthesized. Compound 3 reacted with unsymmetric Zn(II) phthalocyanine (4) to furnish a supramolecular assemble of a Co(II) dimer with six Zn(II) phthalocyanines through azo bridges (5). Co(II) dimeric phthalocyanine with six ferrocenyl groups (7) was obtained by the condensation of 6 with ferrocenylaldehyde. Compounds 3, 5, 6 and 7 were characterized by elemental analysis, ICP-MS, IR, UV Vis and H-1 NMR spectroscopy. The electronic properties of a thin film of the compounds were investigated by impedance spectroscopy and d.c. conductivity measurements as a function of temperature. The a.c. conductivity is found to vary with frequency, omega, as omega(s) with index s <= 1, suggesting a hopping concluction mechanism for 3 and 6. Whereas a frequency independent conductivity was observed for 5. It was found that reducing the nitro group to amines and azo coupling by the asymmetric nitro groups increases the electrical conductivity. The higher conductivity of 5 can be attributed to the increase in the mobility of charge carriers due to overlap of the Tu electron systems along the stacking direction of the molecules. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: dimeric; hexameric; phthalocyanines; supramolecule; impedance spectra; UNSYMMETRICAL PHTHALOCYANINES; COPPER PHTHALOCYANINE; THIN-FILMS; COMPLEXES; AC